An overview of proton exchange membranes for fuel cells: Materials and manufacturing. (22nd May 2022) - Ahmad, Shahbaz; Nawaz, Tahir; Ali, Asghar; Orhan, Mehmet Fatih; Samreen, Ayesha; Kannan, Arunachala M.
Abstract: Due to their efficient and cleaner operation nature, proton exchange membrane fuel cells are considered energy conversion devices for various applications including transportation. However, the high manufacturing cost of the fuel cell system components remains the main barrier to their general acceptance and commercialization. The main strategy for lowering the cost of fuel cells which is critical for their general acceptance as alternative energy sources in a variety of applications is to lower the cost of the electrolyte and catalyst. An electrolyte is one of the most important components in the fuel cell and a major contributor to the cost (>$500/m 2 for commercial Nafion® series). Nafion is widely used as an electrolyte in PEMs, but it has some limitations in addition to high costs such as low proton conductivity, high-temperature performance degradation, and high fuel crossover. Therefore, the development and manufacturing of low-cost and high-performance electrolyte membranes with higher conductivity (∼0.1 S·cm −1 ) at a wider temperature range is a top priority in the scientific community. Recent years have seen extensive research on the preparation, modification, and properties of PEMs such as non-Nafion membranes (SPI, PBI, polystyrene, polyphosphazene, SPAEK, SPEEK, SPAS, SPEN), and their composites by incorporating functionalized CNTs, GO as fillers to overcome their drawbacks. This paper provides a comprehensive review of membrane materials and manufacturing with a focus on PEMs. In particular, the review brings out the basic mechanism involved in proton conduction, important requirements, historical background, contending technologies, types, advantages and disadvantages, current developments, future goals, and directions design aspects related to thermodynamic and electrochemical principles, system assessment parameters, and the prospects and outlook. Graphical abstract: Image 1 Highlights: The PFSA membranes (Nafion®) have been widely used as commercial membranes in PEMFC and DMFC. Nafion membranes possess issues like high cost, high-temperature degradation, oxygen leakage, and methanol permeability. Non-Nafion electrolytes e.g. SPI, PBI, polystyrene, polyphosphazene, SAMCs, & chitosan-based membranes have been reviewed. CNTs and GO-based composites have been proved as promising materials to replace Nafion membranes.